A PENDEKATAN TEORI PESTALOZZI DALAM TERHADAP PENGEMBANGAN KARAKTER ANAK SEKOLAH DASAR: PENDEKATAN TEORI PESTALOZZI DALAM TERHADAP PENGEMBANGAN KARAKTER ANAK SEKOLAH DASAR - Salam, Dudung Abdu; Rukiyati, Rukiyati (jsd: Journal of Society and Development, 2025)
Character education in elementary schools faces complex challenges in integrating moral values with 21st-century competency requirements. This article aims to reconstruct character education models through a synergy between Johann Heinrich Pestalozzi’s educational philosophy and the Pancasila Student Profile framework. Employing a literature review with a philosophical analysis approach, this research explores the "head, heart, and hand" principle as the foundation for children's moral and intellectual growth. The findings demonstrate that Pestalozzi's approach resonates deeply with the Merdeka Curriculum, particularly within the P5 project which emphasizes contextual and humanistic learning. Further discussion reveals the harmonization of Pestalozzian thought with Ki Hadjar Dewantara’s educational concepts that uphold human dignity. The study concludes that this synergistic reconstruction offers a strategic model for educators to design comprehensive, sustainable, and student-oriented learning programs.